Advancing Nuclear Test Verification without Entry into Force of the CTBT. Issue 2 (3rd July 2021) - Sato, Mao
ABSTRACT: Seventy-six years after the atomic bombs exploded over Hiroshima and Nagasaki, the world continues to face challenges to the existing arms control framework, part of the broader problem of the stagnation of multilateralism. There is a desperate need to reinvent the architecture of nuclear disarmament. While it seems almost impossible for the political deadlock to be broken with regard to entry into force of the Comprehensive Nuclear-Test-Ban Treaty (CTBT), the power of science continues to create a unique avenue for confidence-building measures (CBMs) to meet the needs of both nuclear-weapon states and non-nuclear-weapon states. This paper re-examines the value of science as a tool for arms control verification by separating the issue of the CTBT's non-entry into force from the immediate application of its verification regime. The progress of nuclear-test-ban monitoring can be measured against scientific indicators, irrespective of the status of the remaining Annex II countries. The CTBT has already practically satisfied its core function of monitoring nuclear testing with the existing structure. The Preparatory Commission for the Comprehensive Nuclear-Test-Ban Treaty Organization has been progressing as an agent of CBMs, the development of civilian and scientific applications of the verification regime, and a capacity-building effort to attract more states to join the cause, and by doing so, sustaining nuclear-test-ban moratoriums.